Pengaruh Aktivitas Fisik terhadap Kontrol Glukosa Darah Penderita Diabetes Mellitus Tipe 2 - Putri Wahyuningtias; Yovsyah, Yovsyah; Asri Masitha Arsyati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The prevalence of diabetes mellitus (DM) in Bogorse City is 2.1%, which is still higher than the prevalence of DM in Indonesia, Riskesdas 2013 data is 2.0%. The purpose of the study was to determine the effect of physical activity on glycemic control of patients with type 2 DM in the PTM cohort study in Bogor City in 2011-2016. According to the log-rank survival test based on physical activity did not differ significantly with a significance value of 0.941. That survival between groups of sufficient and less physical activity did not differ in survival for poor blood glucose control events. Patients with type 2 DM who are sufficiently physically active have an HR of 0.788 times (95%CI: 0.456-1.360) with a p value of 0.392. This means that patients with type 2 DM who are sufficiently physically active or less do not show a significant difference in blood glucose control. This is because there is a lot of censoring and lost to follow-up, the observation point is quite far spanning 2 years. Continuous health promotion efforts and shorter time span observation point research are needed to produce more precise accuracy effects.